Identification and Cellular Localization of Plasminogen Activators from Human Glomeruli - Angles-Cano, E; Rondeau, E; Delarue, F; Hagege, J; Sultan, Y; Sraer, J D (Thrombosis and Haemostasis, 1985)
The plasminogen activators (PA) and cell types responsible for the fibrinolytic activity of isolated human glomeruli were studied by an indirect spectrophotometric method for plasminogen activation and immunohistological techniques with specific antibodies. Our results indicate that human glomeruli possess the ability to release both tissue-type PA (t-PA) and urokinase (UK). This has been shown for t-PA by quenching its fibrin-dependent activity with rabbit anti-t-PA antibodies and for UK by quenching its fibrin-independent activity with goat anti-UK antibodies. On the other hand, immunohistochemical analysis performed with a murine monoclonal antibody to plasma-t-PA and goat polyclonal antibodies to UK allowed the exclusive localization of t-PA in the endothelial cell lining of the glomerular flocculus and UK in the cytoplasma of glomerular epithelial cells. In addition, arachidonic acid and CaCl2 were shown to enhance glomerular fibrinolytic activity by stimulating the release of either UK or t-PA, respectively. This particular distribution and regulation of glomerular PA’s may be important in the physiopathology of the intra and extracapillary fibrin deposits observed in several glomerulopathies.
Keywords: Glomerular fibrinolytic activity; Vascular plasminogen activator; v-PA tissue plasminogen activator; t-PA; Urokinase; Epithelial cells; Endothelial cells; Isolated human glomeruli